The distributional impact of tax and benefit systems in five African countries. Issue 1 (29th July 2021) - Gasior, Katrin; Leventi, Chrysa; Noble, Michael; Wright, Gemma; Barnes, Helen
Abstract : Purpose: The paper aims to assess the effects of taxes and benefits on inequality and poverty in five African countries: Ghana, Mozambique, South Africa, Uganda and Zambia. Design/methodology/approach: The authors use newly developed micro-simulation models to analyse the distribution and composition of incomes. Findings: The study's results suggest that income-based measures result in higher levels of poverty and inequality than consumption-based measures. The country with the most effective system in terms of reducing income inequality and poverty is South Africa; in Ghana, the tax-benefit system was found to have the smallest impact on inequality. The systems of Uganda, Mozambique and Zambia were estimated to have no poverty-reducing properties; many individuals remain largely unaffected by them as they are too poor to pay direct taxes, and benefits are very modest and narrowly targeted. Originality/value: While consumption data are crucial for measuring poverty, income data are becoming vital for assessing the extent to which tax-benefit policies achieve redistribution in economies where own-consumption is becoming less significant and the share of people in employment is increasing. To the best of the authors' knowledge, this is the first study where poverty and inequality are measured in both terms, for several African countries in a common framework.